Comparison of Metabolomics Expression in The Root and Leaf of Resistance and Susceptible Tomato against Root-Knot Nematode - Enik Nurlaili Afifah; Rudi Hari Murti; Tri Rini Nuringtyas (AGRIVITA, Journal of Agricultural Science, 2020)
The resistant tomato against nematode produces various biochemical compounds associated with the defense mechanisms for nematode attack. These compounds allegedly expressed in all cells not only in the infected area. These metabolites are useful for plant development program to point out the candidate traits based on specific metabolites. This study aimed to compare expression of metabolomics as defense mechanism in root and leaf of the plant. Four cultivars consisted of the resistant [GM2 and F1 (a cross GM2 and Hawaii 7996)] and susceptible (Gondol Putih and Gondol Hijau) were used as plant materials. Fifty mg of freeze-dried of root and leaf were taken for assessing 1H-NMR (Nuclear Magnetic Resonance) for metabolomic analysis. Tomato roots resulted in 16 metabolites, while in the leaf detected 15, including amino acid, sugar, and aromatic compounds. Both root and leaf showed the same metabolites that play an important role in nematode-resistant mechanism, these metabolites were α- and β-glucose, and caffeic acid. These compounds had the same concentration within the root and leaf. It is implied that the metabolites associated with defense mechanism of tomato plants against nematode not only expressed locally in the infected area but also produced by not infected tissues throughout the plant.